2019
DOI: 10.1186/s12871-019-0802-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opioid-free anaesthesia on post-operative period in cardiac surgery: a retrospective matched case-control study

Abstract: Background No study has been conducted to demonstrate the feasibility of an opioid-free anesthesia (OFA) protocol in cardiac surgery to improve patient care. The aim of the present study was to evaluate the effect of OFA on post-operative morphine consumption and the post-operative course. Methods After retrospectively registering to clinicaltrial.gov (NCT03816592), we performed a retrospective matched cohort study (1:1) on cardiac surgery patients with cardiopulmonary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 33 publications
1
67
1
1
Order By: Relevance
“…In our study, patients with a low-opioid anesthesia scheme had a shorter duration of mechanical ventilation and stay in the ICU, which was consistent with the work of Guinot's et al, who used lidocaine, dexamethasone, and ketamine for the low-opioid anesthesia scheme [21].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, patients with a low-opioid anesthesia scheme had a shorter duration of mechanical ventilation and stay in the ICU, which was consistent with the work of Guinot's et al, who used lidocaine, dexamethasone, and ketamine for the low-opioid anesthesia scheme [21].…”
Section: Discussionsupporting
confidence: 91%
“…Current research has shown that a lower dose of opioids has a positive effect on p/o recovery in patients who have undergone cardiac surgery with ABC [ 15 ], but further randomized studies are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…noted that the non-opioid group of patients showed higher intraoperative use of antihypertensive agents. They used ketamine, dexamethasone, and lidocaine in their regimen [ 15 ]. In our study, we did not note such hemodynamic features in the indicated scheme of multimodal low-opioid anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses. Sample size calculation was based on a previously published study and institutional database 7 . The inclusion of 42 patients was needed to demonstrate a difference of 30% in the total dose of sufentanyl for a mean dose of 80 µg (± 27) between the two groups, with a power of 90% and a two-tailed p-value of 0.05.…”
Section: Randomizationmentioning
confidence: 99%